Perceptions of task-based approach on EFL students at Hoa Thuan high school - Nguyễn Thị Thảo (Trường Đại học Trà Vinh, 2020)
The study is aimed to achieve the following objectives: To examine the students’ understanding of task-based approach on language learning? To explore students’ perceptions on learning task-based language learning in classroom practice?